Tacit knowledge in organizational learning - Busch, Peter, 1967- (IGI Pub., 2008)
"This book offers academians and practitioners an illustration of the importance of tacit knowledge to an organization, presenting a means to measure and track tacit knowledge in individuals and recommendations on firm attributes and their ideal utilization of the tacit knowledge resource"--Vydavatelská anotace